Maslahah Mursalah In Islamic Economic Philosophy - Agam Darwis, Sarah Zettira; Syahidah Rahmah (International Journal of Sharia Business Management, 2025)
Maslahah mursalah is a fundamental idea used to support the development of Islamic economics. This principle can also be an answer to current economic challenges. Refers to the public benefit, which is not explicitly regulated by Islamic law, providing a flexible framework for formulating economic solutions based on Islamic principles. This article aims to highlight the relevance and application of the Maslahah mursalah concept in various sectors of the Indonesian economy, including sharia banking, investment, and sustainable economic development. This article also aims to discuss how economic policy concepts can support public benefit and sustainability. This article contributes to expanding insight and provides an overview of the concept of Maslahah Mursalah in the diverse context of Islamic economics in Indonesia. Apart from that, the ideas of Maslahah mursalah in Islamic economic philosophy can provide an additional in-depth understanding of the economy, which can be used as a supporting instrument in developing economic policies that are in line with Islamic principles in particular.